Education of Primary Class Students in Spiritual and Moral Spirit Issues (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In the Republic of Uzbekistan, the education reform is aimed at improving the morale of individual personnel, improving modern teaching and upbringing methods. As a point of view, both the class and the moral and ethical qualities educate the staff to solve the problem described in the article is the movement for help